Analysis on temperature setting for extruding polylactic acid using open-source 3D printer - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (Asian Research Publishing Network (ARPN), 2017)
The Rapid Prototyping (RP) technology has been developed since its original introduction, leading to a significant improvement in the manufacture of high-quality finished products. Fused deposition modeling (FDM) is a RP technology that has been widely used because of the flexibility of the FDM process. Despite the popularity of the FDM machines, cost remains a major issue, motivating the development of low-cost open-source 3D printing. However, the system and process of open-source 3D printing needs to be investigated, particularly along the highly complex liquefier; observation of the material flow inside the liquefier is essential for this purpose. This paper examines the temperature distribution of the liquefier and the flow behavior of the material inside the liquefier using finite element analysis (FEA). The liquefier temperature must be at 190 °C because higher temperatures cause the material to burn and lower temperatures may be detrimental for the extrusion process. Therefore, this study focuses on identifying the optimum printing temperature for the widely used polylactic acid (PLA) filaments. A new cylindrical liquefier design has been proposed to achieve a better heat distribution, and an optimum printing temperature of 190 °C (463.15K) has been suggested for extruding PLA material using open-source 3D printing.